Strategic yet delicate: the dilemma of involving health workers in facilitating birth registration in Indonesia - Clara Siagian; Wenny Wandasari; Feri Sahputra; Santi Kusumaningrum (BMC, 2019)
Abstract Background Birth registration provides the basis for population data. Previous studies have examined that collaboration between the health sector and civil registration can help improve birth registration rate. However, there was a little exploration into health workers' understanding of civil registration and vital statistics (CRVS) and their perceived role in it. This study aims to fill this gap by focusing on the perspective of both health personnel in a managerial position and those who are involved in direct service provision to the community. Finally, we discussed the opportunities and challenges to strengthen the birth registration presented by health workers' diverse views. Method This study uses a qualitative approach through semi-structured in-depth interviews with 23 provincial to village health personnel in Pangkajene Kepulauan (Pangkep) district of South Sulawesi province. The participants were selected through consultation with the Department of Planning and the head of the Department of Health at provincial and district level based on the relevance of their position with CRVS. At the frontline level, the informants were identified using a snowballing technique and recommendation from community members. Results This study finds that at the village level, health workers perceive CRVS as important since it supports them in delivering healthcare to community members. They see identification document like birth certificate as crucial for healthcare seekers to access the government's health insurance and with that, proper and affordable treatment. Some health workers have been facilitating birth registration on a discretionary basis. Local health officials agree that accurate birth data lead to effective planning and financing for healthcare services and insurance. Despite the positive perception of birth registration, the majority of health workers do not want the additional burden for registering births. Health officials, however, are more open to taking some responsibilities. Conclusion This study concludes that the level of health workers' understanding and appreciation of the CRVS system provides opportunities to engage them systematically in birth registration. It recommends that institutionalizing health workers' participation in birth registration must consider their current workload, revision of legal instruments, capacity building plan, and operable linkage with civil registration authority.